POLA KOMUNIKASI PASANGAN SUAMI ISTRI DALAM PERKAWINAN BEDA AGAMA - Wisnu Widjanarko (Indonesian Journal of Dialectics, 2011)
Inter-faith marriage, such as Islam-Catholic marriage has been a certain reality for we cannot deny its existence in the society even though some people think of it as unusualness. The principal interpretation of each religion, the rule of law, and the potential of horizontal latent conflict in the community marginalize that marriage. However, it is interesting that the practice exists and becomes a choice for couples who want to get married. This study attempts to explore the communication patterns of the inter-faith couples. Using social phenomenology approach, the researcher applied in-depth interview to elaborate the comprehension of ten informants from Javanese involved, especially the comprehension on their account of their marriage and their communication experience authentically in the adaptation process during the marriage. The result of the research shows two inter-faith account in practice; understanding and social justification account. The former means a love-based account which states that someday everybody will accept the reality, while the latter means a love-based motive and there is a belief that there is nothing different in that marriage. Every inter-faith marriage doer has low-fidelity religious affiliation or they may have a pluralistic theological interpretation with minimal resistance from significant other. The researcher also reveals that communication experience is an inseparable inter-subjective experience in conflict management and decision making process to reach the agreement on some problems they have, such as the wedding ceremony, the religion symbols in their house, the religious education for their children, the daily ritual and religious celebration, and also the problem in communicating their family identity to their neighborhood.